Mathematical Modeling of NMRP of Styrene - Divinylbenzene over the Pre and Post Gelation Periods Including Cyclization - Leandro G. Aguiar (2013)
Nitroxide-mediated polymerization of styrene-divinylbenzene has been modeled using generating functions of length distributions, pseudo-kinetic propagations, and numerical fractionation with the crosslinking rate depending on generation. Cyclization reactions are tackled by balances of sequences, yielding fair predictions of the measured pendant double bond concentration. With reduction in crosslinking, agreement for the experiments at 90 8C between predicted and measured weight-average, molecular weight, and weight fraction of gel is observed. A much higher relative crosslinking reactivity is observed at 130 8C as compared to 90 8C, likely an effect of the chain mobility.